Development of new or worsening headache after cochlear implant activation: A hypothesis-generating pilot study of incidence, timing, and clinical factors. (24th August 2020) - Riggins, Nina; Chae, Ricky; Levin, Morris; Ehrlich, Annika; Sawhney, Henna; Polite, Colleen; Goadsby, Peter J
The objectives of the study are to investigate the incidence of new or worsening headache after cochlear implant (CI) surgery and activation and to determine whether there are predictors of associated headache. We performed a cross-sectional survey of patients who had CI surgery. The frequency and severity of headache, onset of headache relative to surgery and device activation, medication use, family history, headache triggers, and accompanying cranial autonomic symptoms were recorded and analyzed. Thirty-seven subjects were enrolled. In the time period after CI surgery but before CI activation, none reported a new headache and four (11%) reported a worsening headache. After CI activation, six (16%) developed new headache and five (14%) developed worsening headache. These 11 subjects also experienced a significantly higher mean of 6.3 headache days/month following CI activation ( p < 0.009). Providers should be aware that new or worsening headache can be reported following CI activation, although not immediately following CI surgery.